Developing Microsoft Access Based- E-Siska Learning Media for Vocational High School Students - Putri, Farah Nabilla; Pahlevi , Triesninda (Universitas Negeri Surabaya, 2023)
This study aims to develop learning media for Microsoft access-based electronic archives applications and assess its effectiveness on 11th-grade students’ learning outcomes at State Vocational High School 1 Surabaya. This development research uses an experimental approach to use the ADDIE model development method (Analyze, Design, Develop, Implement, Evaluate). The results of this research are known to average the results of expert validation of learning media by 94% with a very feasible category. The results of student responses obtained an average of 89% with an extreme category. The results of the N-Gain Score test were 59% with a fairly effective category and the results of the Independent Sample t-test with the results of tobserved (2.936) > ttable (1.671). Therefore, it can be concluded that the learning media for Microsoft access-based electronic archives applications effectively improves student learning outcomes.